The Influence Of Discipline On The Performance Of Sports Teachers At SMK Karawang Regency - Irfan rahman (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Based on the results of the SMK Teacher Competency Test (UKG) in Karawang Regency in 2022 of 57.01, while the Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 29 article 9 paragraph 1 explains that the minimum score for passing the UKG is at least 70, and it can be said that the UKG score is below standard. Therefore, the researcher aims to determine and analyze the effect of discipline on the performance of sports teachers at SMK Karawang Regency. The method used is a survey method with a quantitative approach. Data collection in the form of questionnaires distributed to the sample, and the analysis techniques used are descriptive statistics, and inferential. The results showed the effect of discipline on the performance of sports teachers with a tcount value of 11.969 while the ttable value is 2.048. It can be stated that if tcount> ttable then h0 is rejected and ha is accepted, namely there is a direct influence of discipline on the performance of sports teachers at SMK Karawang Regency.